Efficacy of a complex plant-based preparation for poultry mycotoxicosis - E. V. Kuzminova; E. P. Dolgov; M. P. Semenenko; P. V. Miroshnichenko (Ветеринария сегодня)
The article presents results of efficacy studies for a complex plant-based preparation for poultry mycotoxicosis. Feed additive fibralin contains polysaccharides (dried sugar beet pulp) and phospholipids (rapeseed lecithin) in the proportion 4:1. Eighteen-day-old “Ross-308” broiler chickens with average weight of (665.10 ± 4.28) g were tested, since such mycotoxins as T-2 toxin, zearalenone and aflatoxin B1 were detected in their feeds. Maximum admissible level of each toxin was not exceeded, however, their cumulative effect on poultry resulted in mycotoxicosis. Use of fibralin in the feed (3 kg per one ton) for 10 days reduced clinical signs of intoxication, increased flock survival by 13.5% and stimulated body weight gain by 15.8%. Pharmacological effect of fibralin was demonstrated by improvement of blood morphobiochemical parameters in poultry, i.e. reduction of leukocytes by 19.3% and cholesterol by 13.6%; and an increase in the number of erythrocytes by 19.4%, hemoglobin by 8.1% and calcium by 9.5%. Antitoxin therapy had a positive effect on liver structure and functions and that fact was confirmed by a decrease in aminotransferase level in serum and normal levels of total protein. The data obtained may justify the use of this natural bio-preparation as a product with antitoxic and hepatoprotective properties and the use of fibralin for mycotoxicosis treatment of poultry.